Virgil at Appleton House. - Guy-Bray, Stephen (English Language Notes, 2004)
Presents literary criticism which examines the Virgilian genres in the poem "Upon Appleton House" by Andrew Marvell. Discussion of the use of the name Thestylis; Epic elements of the poem; Resemblance between Marvell's Mary and Virgil's Venus in "Aenid."